"Is it true that Digital Marketing, Brand Image and Product Quality can influence the Decision on the Use of Hello Cards." - Wiludjeng SP, Sri (International Journal of Psychosocial Rehabilitation, 2020)
Technological developments in the current era of globalization are pushing information more rapidly. This will have an impact on the increasingly dramatic development of business activities. Every company tries to improve or change its marketing strategy in order to attract and retain customers. Among the marketing strategies used by the company are digital marketing, brand image, and product quality; this is expected to be able to improve the decision to use halo cards in carrying out their daily activities. This study aims to find out how consumer responses to digital marketing, how consumers respond to brand image, and how responses about the quality of halo card products influence the decision to use a halo card. The methods used in this research are descriptive and verification methods. Data compilation techniques include distributing questionnaires, interviews, and observations. The sampling technique used was accidental sampling. The tool used is multiple regression. The results showed that digital marketing, brand image, and product quality influence the decision to use halo cards positively and significantly. This is because digital marketing used by Telkomsel companies can be accepted by consumers and meet consumer expectations, as well as brand image and quality of halo card products are trusted because they have a strong signal.